2019
DOI: 10.1590/1678-4162-10339
|View full text |Cite
|
Sign up to set email alerts
|

Biosseguridade para sistemas de produção de peixes em tanque-rede em função da colmatação agravada por Limnoperna fortunei

Abstract: RESUMO Este trabalho avaliou a colmatação por Limnoperna fortunei em diferentes materiais para confecção de telas de arame, a dinâmica da colmatação pelo molusco e a relação custo-benefício dos materiais usados em tanques-rede. Utilizaram-se amostras de telas de simples torção de malha 19mm, de cinco tipos diferentes de revestimentos, colocadas na barragem de Salto Caxias, no Rio Iguaçu, estado do Paraná, entre julho de 2012 e julho de 2014. A cada seis meses, foi verificado o ganho de peso das telas em razão … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…The ceramic material coated with base paint with commercial zinc oxide showed the least encrustations concerning paints with the presence of copper and others with anti-fouling properties, proving the good efficiency of zinc in controlling the fouling of golden mussel. Vianna et al (2019) evaluating the clogging by golden mussel in different materials for making screens of net cages, found the lowest levels of clogging in Bezinal screens concerning PVC-coated screens. However, the authors highlight the lower cost/year of the PVC screen compared to Bezinal.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ceramic material coated with base paint with commercial zinc oxide showed the least encrustations concerning paints with the presence of copper and others with anti-fouling properties, proving the good efficiency of zinc in controlling the fouling of golden mussel. Vianna et al (2019) evaluating the clogging by golden mussel in different materials for making screens of net cages, found the lowest levels of clogging in Bezinal screens concerning PVC-coated screens. However, the authors highlight the lower cost/year of the PVC screen compared to Bezinal.…”
Section: Discussionmentioning
confidence: 99%
“…Cage fouling increases production costs as they reduce the durability of structures and require frequent cleaning of the screens. Furthermore, the fouling blocks water exchange from net cage and biologically analyzing can be a source of contamination or pollution for aquaculture in reservoirs (Costa et al, 2018;Freire and Marafon, 2018;Vianna et al, 2019). Rezende Ayroza et al (2019), when investigating the cage fish farm as a vector for golden mussel invasion, concluded that fish breeding in cages contributes to the establishment of the L. fortunei in reservoirs by elevating larval density and the nutritional status of the mollusk.…”
Section: Introductionmentioning
confidence: 99%